2009
DOI: 10.1002/pmic.200700288
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of transcriptome and proteome data as a tool for the identification of candidate biomarkers in renal cell carcinoma

Abstract: Results obtained from expression profilings of renal cell carcinoma using different “ome”-based approaches and comprehensive data analysis demonstrated that proteome-based technologies and cDNA microarray analyses complement each other during the discovery phase for disease-related candidate biomarkers. The integration of the respective data revealed the uniqueness and complementarities of the different technologies. While comparative cDNA microarray analyses though restricted to upregulated targets largely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 56 publications
1
37
0
Order By: Relevance
“…identify RCC-specific biomarkers have investigated at gene and protein levels either in cells, primary culture [10] or stable lines [11], or in tissues [12][13][14]. These candidate markers identified by these strategies may not be present or their profile in biological fluids (e.g., urine, serum and plasma) may not be altered, as would be necessary for screenings based on biological material collected with noninvasive or less invasive methods.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…identify RCC-specific biomarkers have investigated at gene and protein levels either in cells, primary culture [10] or stable lines [11], or in tissues [12][13][14]. These candidate markers identified by these strategies may not be present or their profile in biological fluids (e.g., urine, serum and plasma) may not be altered, as would be necessary for screenings based on biological material collected with noninvasive or less invasive methods.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Highly sensitive profiling studies require a combination of MS and separation technologies [40]. RCC-specific biomarkers have been searched in primary culture, stable lines, and in solid biological material (primary cell cultures, stable cell lines and tissues) with classical proteomics approaches [10][11][12][13]. Sample fractionation can be used to increase the number of proteins detectable with MS (e.g., enriches for the low abundant proteins) such as by bi-dimensional liquid chromatography (MudPIT) or to reduce the sample complexity by activated surfaces.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…13 However, in the neoplastic setting only the presence of the 36-kDa isoform of AnxA3 has been described until now. Thus, considering that there are very limited data concerning AnxA3 in kidney and RCC 14 and that deregulation of HIF pathways plays a key role in the pathogenesis of RCCcc, 3 we initiated the study of AnxA3 in primary cell cultures of RCC and normal cortex. With the combination of different technical approaches we demonstrated a differential expression pattern, correlated with HIF-1␣ expression, of two AnxA3 isoforms originating by an alternative splicing of exon III in RCC and normal renal tubular cells.…”
mentioning
confidence: 99%
“…ANXA4 could play an important role in regulating the cellular functions at the level of cell-cell interaction, cell adhesion and motility and, although increased protein expression level of ANXA4 has been confirmed in ccRCC by global proteomic analysis (Seliger et al, 2009), its possible implication in the carcinogenesis of RCC deserves further studies. Carbonic anhydrase 9 (CA9) is a transmembrane member of the carbonic anhydrase family that catalyses the reversible hydration of carbon dioxide into bicarbonate and a proton, thus enabling tumor cells to maintain a neutral pH despite an acidic microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…As recently reviewed by Pal et al (Pal et al, 2010), several gene expression and proteomic studies carried out on fresh and archival ccRCC tissues (Perroud, 2009;Seliger, 2009) evidenced a series of molecular processes and pathways involved in ccRCC tumorigenesis (Banumathy & Cairns, 2010) and indicated that ccRCC progression is strictly associated to the adaptation of cancer cells to low oxygen levels (Baldewijns, 2010;Bristow & Hill, 2008) and to their continuous proliferation even in the presence of compromised DNA repair mechanisms (Semenza, 2008). These results find an additional confirmation from the analysis of genomic data presented in this chapter.…”
Section: Discussionmentioning
confidence: 99%